The Relationship between Job Seekers’ Perception and E-Recruitment Adoption - Mohd Arif, Illi Syahirah; Salim, Siti Aisyah (Research in Management of Technology and Business, 2025)
This study explored job seekers’ attitudes and perceptions toward online platforms, examining how these platforms transformed traditional recruitment methods and provided organizations with innovative ways to connect with potential candidates. In today’s rapidly evolving technological landscape, organizations need to understand how job seekers utilized e-recruitment sites in their job search. With approximately 649,300 job seekers relying on online platforms to streamline their job search, the growth of e-recruitment underscored the increasing demand for more efficient hiring processes.The research highlighted how e-recruitment sites revolutionised traditional recruitment methods, offering organizations new avenues to engage with top talent. The data were analysed using the Statistical Package for Social Sciences (SPSS) and collected through a quantitative research method, utilizing both an online survey and the direct distribution of questionnaires to potential candidates. From the analysis, the relationship between job seekers’ perceptions and e-recruitment adoption was found to be strong. The correlation between advertisement placement and e-recruitment adoption was 0.794, while the correlation between advertisement information and e-recruitment adoption was 0.812, and the correlation between interest in jobs and e-recruitment adoption was 0. 870.All three correlations were statistically significant, indicating a strong relationship between these factors and the adoption of e-recruitment platforms. This research helped in understanding what motivated job seekers to use e-recruitment platforms, offering useful insights for improving hiring strategies. The findings showed that e-recruitment revolutionized the job search process, offering job seekers greater access to opportunities, increased convenience, and improved communication. This shift toward e-recruitment highlighted the importance of using technology to improve the hiring process.